2007
DOI: 10.1016/j.drugalcdep.2007.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of social support and self-efficacy in treatment outcomes among clients with co-occurring disorders☆

Abstract: Individuals with co-occurring substance use and psychiatric disorders have a more severe clinical course and poorer outcomes than do individuals with one disorder. In an attempt to find intervening variables that may contribute to improvement in treatment outcomes among individuals with cooccurring disorders, we investigated the roles of social support and self-efficacy in a sample of 351 clients with co-occurring disorders in residential drug abuse treatment programs (53% male; 35% African American, 13% Hispa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 53 publications
11
90
1
4
Order By: Relevance
“…These mothers also distanced themselves from drinking environments and friendships based around alcohol, replicating previous findings [37]. Seeking out and befriending abstinent others may mitigate against potential factors of inferiority and threats to esteem brought about by experiencing issues related to alcohol problems.…”
Section: Factors Important In Sustaining Abstinencesupporting
confidence: 77%
“…These mothers also distanced themselves from drinking environments and friendships based around alcohol, replicating previous findings [37]. Seeking out and befriending abstinent others may mitigate against potential factors of inferiority and threats to esteem brought about by experiencing issues related to alcohol problems.…”
Section: Factors Important In Sustaining Abstinencesupporting
confidence: 77%
“…Por otra parte, las personas de edad que presentan déficits en lo que respecta a sus redes de apoyo han mostrado una mayor tendencia al abuso de drogas (Allard, Allaire, Leclerc & Langlois, 1995;Warren, Stein & Grella, 2007) y de alcohol (Brennan & Moos, 1990;Schonfeld & Dupree, 1991) y se ha identificado a la insatisfacción con el apoyo social del cual se dispone como una de las variables predictoras de la ideación suicida en los adultos mayores (De Leo & Ormskerk ,1991;Mireault & De Man, 1996;Vanderhorst & Mc Laren, 2005).…”
Section: Impacto Del Apoyo Social Sobre El Bienestar De Los Adultos Munclassified
“…Studies has shown that social support is considered as an important factor for positive and remunerative experiences which finally leads to adolescents' self-worth and self-esteem level. A research result indicated that there is significant relationship between perceived social support and adolescents' adaptability [16]. Masoudnia concluded that there is negative and significant relationship between the perceived social support and depression [17].…”
Section: Introductionmentioning
confidence: 99%
“…Such adolescents who do not observe the society's ethics and customs will face serious problems such as anti-social behaviors and committing crimes as they begin their ages of youth or university's period [8]. Considering that perception of social interaction, perceived social support and social acceptance play important roles in adolescents' psychological health and aggression [10,16] and since the level of boy adolescents' aggression is higher than girls [24], investigation of these variables relationships with adolescents' aggression, particularly in boy adolescents seems necessary. Considering the significance of this topic and the mentioned facts, this study was aimed to investigate the relationship between perception of social interaction, perceived social support and social acceptance with aggression among adolescents…”
Section: Introductionmentioning
confidence: 99%